2D Ferromagnetism: Robust Above‐Room‐Temperature Ferromagnetism in Few‐Layer Antimonene Triggered by Nonmagnetic Adatoms (Adv. Funct. Mater. 15/2019). (9th April 2019) - Tang, Xian; Hu, Liang; Fan, Touwen; Zhang, Le; Zhu, Liping; Li, Hui; Liu, Haoliang; Liang, Jiyuan; Wang, Kedong; Li, Zhongjun; Ruan, Shuangchen; Zhang, Yupeng; et al.
Abstract : In article number1808746, Yu‐Jia Zeng, Han Zhang, and co‐workers propose a nonmagnetic fluorine doping strategy to induce stable long‐range ferromagnetic orders in electrochemically synthesized 2D antimonene. The fluorinated antimonene exhibits a Curie temperature as high as 717 K. The study constitutes a nonmagnetic control of robust above room‐temperature ferromagnetism in monoelemental 2D semiconductors.